Gen Z's Behavior Towards Digital Culinary Brands on TikTok - Nanis Susanti; Enny Istanti (International Journal of Economics, Commerce, and Management, 2025)
This study aims to explore the behavioral dynamics of Generation Z (Gen Z) toward digital culinary brands on TikTok, a platform increasingly central to youth consumer engagement. The research investigates how Gen Z interacts with, interprets, and forms relationships with culinary content in a digital environment shaped by algorithmic trends and participatory culture. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with 12 Gen Z participants aged 18–24 years who actively engage with culinary brand content on TikTok. Additional data were obtained from observational analysis of brand-related content and user interactions on the platform. Thematic analysis revealed three core themes: emotional engagement with sensory-rich food content, digital consumption as identity performance, and expectations of brand authenticity and interactivity. Participants expressed strong affective responses to visually appealing and immersive content, linked their brand preferences to personal values and social identity, and favored brands that demonstrated responsiveness, humor, and human-like interaction. These findings highlight the role of TikTok not only as a marketing tool but as a cultural space where brand perception and loyalty are socially constructed. This study contributes to the theoretical understanding of consumer engagement by situating Gen Z’s behavior within a sociocultural and digital framework. Practically, it offers insights for culinary brands to develop more authentic, interactive, and value-driven content strategies. The findings also suggest implications for digital marketing policies and content regulation. Future research is recommended to explore cross-platform behaviors and cultural variations in digital brand engagement.